Accurate dating of tropical secondary forests using wood core Δ14C in Malaysia - Ichie, Tomoaki; Igarashi, Shuichi; Tamura, Sae; Takahashi, Ai; Kenzo, Tanaka; Hyodo, Fujio; Tayasu, Ichiro; Meleng, Paulus; Azani, Mohamad Alias; Wasli, Mohd Effendi; Matsuoka, Masayuki (Elsevier BV, 2023)
Following the widespread loss and degradation of old-growth forests throughout the tropics, the area of secondary forests has expanded significantly in the past few decades. Understanding the history of vegetation modification is necessary for the proper maintenance and management of tropical secondary forests. Although satellite image analysis is an effective method for evaluating such changes, observations in tropical regions are limited by dense cloud coverage, and it is difficult to estimate the timings of forest disturbances based on annual rings because the climate is aseasonal and trees do not form clear annual rings near the equator in Southeast Asia. In this study, we developed a new, highly accurate technique for dating tropical secondary forests after disturbances such as shifting cultivation and forest fire in Malaysia based on Δ14C content of trees. We established 29 plots (20 m × 20 m) in secondary forests in six areas of Malaysia, mainly in Sarawak, and used time-series satellite images to determine the most recent disturbance with temporal accuracy of <6 years. We collected wood core samples from one or two trees with the largest diameter in each plot and measured the Δ14C content of their pith to estimate tree ages. We detected a significant positive correlation between tree age estimated by Δ14C dating and the period since the latest disturbance according to the time-series satellite images. The Δ14C-based age estimates were approximately five years younger than those obtained by satellite image dating. This difference is considered to indicate the time required for land use shifts after clear cutting or forest fire, and for tree species invasion after land abandonment. Together, our results revealed that the Δ14C method may be used to date tropical secondary forests after disturbance with high accuracy, even in aseasonal tropical rainforest areas.